2007
DOI: 10.1021/je700152c
|View full text |Cite
|
Sign up to set email alerts
|

1-Butyl-3-methylimidazolium Tosylate Ionic Liquid:  Heat Capacity, Thermal Stability, and Phase Equilibrium of Its Binary Mixtures with Water and Caprolactam

Abstract: Heat capacity for 1-butyl-3-methylimidazolium tosylate [C4mim][Tos] in the temperature range (5 to 370) K has been measured by adiabatic calorimetry. Temperatures and enthalpies of its phase transitions have been determined. Thermodynamic functions have been calculated for crystalline and liquid states. The thermal stability of [C4mim][Tos] has been determined by scanning calorimetry. Mutual solubility in binary mixtures of [C4mim][Tos] with water and caprolactam has been investigated, and the activity coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 10 publications
(22 reference statements)
1
40
1
Order By: Relevance
“…[21] Such a melting point depression may originate from impurities introduced during synthesis and/or moisture uptake during storage or measurement. Organic salts can be very hygroscopic, [20,22] suggesting that even short exposure to air may lead to significant water uptake. If water or solvent molecules form stoichiometric or non-stoichiometric co-crystals with the salt, this may be overlooked, especially if the crystal structure was not determined.…”
Section: Contaminationmentioning
confidence: 99%
“…[21] Such a melting point depression may originate from impurities introduced during synthesis and/or moisture uptake during storage or measurement. Organic salts can be very hygroscopic, [20,22] suggesting that even short exposure to air may lead to significant water uptake. If water or solvent molecules form stoichiometric or non-stoichiometric co-crystals with the salt, this may be overlooked, especially if the crystal structure was not determined.…”
Section: Contaminationmentioning
confidence: 99%
“…The C vib values were calculated in a harmonic approximation using these frequencies. The set of frequencies for the most stable conformers of [bmim] + and anions [7,10] and in this work were used. The equation C p ðliqÞ=J Á K À1 Á mol À1 ¼ ½7:71 À 2:12 Á 10 À2 T À 1:17 Á 10 À2 M þ 2:27 Á 10 À5 T 2 þ 1:11 Á 10 À5 TM þ 9:77…”
Section: Calculationmentioning
confidence: 99%
“…Especially, this concerns dependence of thermal properties on the nature of the anion. Earlier, the authors investigated a series of 1-butyl-3-methylimidazolium ([bmim] + ) ILs [6][7][8][9][10]. It was found that thermal behavior of ILs is strongly dependent on the nature of the anion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aprerequisitefor the suitability of asalttoact as ionic liquid is its low melting pointthat is conveniently achieved by the introduction of long perfluoroalkylalkyl chainsinto simple nitrogen-containing organic moieties and crystallizing theresulting cations by means of bulkier anions suchastosylate [1]. In our continued interest in creating simplerd erivatives of nitrogen compounds that might act as ionicliquids [2] motivated us to synthesize the title compound andelucidateits crystal structure by means of adiffraction study.…”
Section: Discussionmentioning
confidence: 99%